Legal Protection of “Hashtag” Under Trademarks Rules “Analytical Study in The Syrian Legal System” (Damascus University Journal for legal sciences, 2025)
Hashtags emergence in the virtual world and on social media has contributed to mobilizing public opinion towards supporting or rejecting many issues, ideas, and events at the local and international standards. This is something that individual traders and commercial companies, as well as owners of small and medium-sized investment projects, all the way to the largest multinational economic establishments at the national and global levels. The importance of hashtags in marketing various products and services became apparent, which contributed to doubling the chances of achieving profits, and thus making any commercial project successful with less effort and cost, by reaching the best results that the merchant seeks in terms of attributing these goods or services to him not to any other competitor in the market in a way that exceeds spatial and temporal boundaries in their traditional sense, which makes it necessary for legal researchers to look at the hashtag from a different angle as it is one of The most advanced form of trademarks in the modern era, with the various legal implications that result from it, the most important of which is its benefit from the protection provisions established for trademarks in the Syrian Arab Republic, assuming that it fulfills the objective and formal conditions for enjoying this protection, and the consequent possibility of implementing civil or penal protection for infringing the hashtag owner rights, whether the illegal act  occurs in the real world or the virtual world.
Keywords: Hashtags; Trademark; Terms Of Legal Protection; Unfair Competition; Penal Sanctions